Methodology of Using CAx and Digital Twin Methods in the Development of a Multifunctional Portal Centre in Its Pre-Production Phase - Petr Bernardin; Zdenek Hajicek; Petr Janda; Josef Kozak; Frantisek Sedlacek; Vaclava Lasova; Jiri Kubicek (Applied Sciences)
The latest phase of the industrial revolution (Industry 4.0 and Industry 5.0) involves a large number of key areas that are crucial to improving the performance of technical systems. Computer-aided design and computer-aided engineering are important in their development and the digital twin of systems is one of the key tools for optimising their properties. This research deals with the use of these tools in the development of a machine tool. Nowadays, these tools are usually used separately. The aim of this work was therefore to propose a widely applicable methodology that would suitably combine the previously mentioned tools and thus use their synergistic effect. The proposed methodology was used on a specific machine, namely, a multifunctional portal centre, where features of computer-aided engineering (modelling, topology optimisation, stiffness and stress analyses, modal analyses, and analytical calculations) were combined with tools using the digital twin. The advanced simulations and the creation of the digital twin were performed in the pre-production phase of the machine and are described in detail within this paper. The aforementioned methodology was used to obtain and verify the final dimensions of the developed machine centre, which were the expected results. The proposed dimensions were verified in this way in terms of the mechanical properties of the designed machine (stiffness, strength, and modal properties), in terms of the suitability for machining the specific part, and in terms of the moved masses and drive parameters.